2017
DOI: 10.1534/g3.117.043786
|View full text |Cite
|
Sign up to set email alerts
|

Two Variants inSLC24A5Are Associated with “Tiger-Eye” Iris Pigmentation in Puerto Rican Paso Fino Horses

Abstract: A unique eye color, called tiger-eye, segregates in the Puerto Rican Paso Fino (PRPF) horse breed and is characterized by a bright yellow, amber, or orange iris. Pedigree analysis identified a simple autosomal recessive mode of inheritance for this trait. A genome-wide association study (GWAS) with 24 individuals identified a locus on ECA 1 reaching genome-wide significance (Pcorrected = 1.32 × 10−5). This ECA1 locus harbors the candidate gene, Solute Carrier Family 24 (Sodium/Potassium/Calcium Exchanger), Mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Loss-of-function mutations in this gene led to reduced melanin concentration in zebrafish ( Lamason et al, 2005 ). However, a non-synonymous mutation in the exon 2 of slc24a5 in a horse generated bright orange-colored eyes ( Mack et al, 2017 ). A recent study also reported that a non-synonymous mutation in slc24a5 significantly correlated to skin color in African human populations ( Crawford et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Loss-of-function mutations in this gene led to reduced melanin concentration in zebrafish ( Lamason et al, 2005 ). However, a non-synonymous mutation in the exon 2 of slc24a5 in a horse generated bright orange-colored eyes ( Mack et al, 2017 ). A recent study also reported that a non-synonymous mutation in slc24a5 significantly correlated to skin color in African human populations ( Crawford et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fernández et al [59] found evidence that OCA2 has an effect on skin color intensity in red strain of Iberian pigs. OCA2 and HERC2 were suggested as candidate genes for the leopard spotting pattern [60] and for the equine “Tiger-eye” phenotype by Kowalski and Bellone [61] but could not be confirmed [62]. To our knowledge, no investigation on the influence of OCA2/HERC2 on the mealy phenotype, as exhibited by the Exmoor Pony, has been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA utilized for the GWAS was isolated from hair roots using the Gentra Puregene DNA isolation Kit as previously described [13]. DNA used for genotyping and validating variants of interest was isolated according to a crude hair lysis protocol [14].…”
Section: Methodsmentioning
confidence: 99%